Peranan Guru dalam Membentuk Akhlak Santri di Pondok Pesantren Putra Al-Maliki 1 Bahrul Ulum Tambak Beras Jombang - Hakim, Denny Nuril; Waqfin, Mohammad Saat Ibnu (Lembaga Yasin AlSys, 2025)
This study is motivated by the public assumption that pesantren (Islamic boarding schools) can make a significant contribution to society through the moral education of students, thereby shaping good character and increasing students' motivation for worship to realize a generation with noble character (akhlakul karimah) and broad vision while upholding humility (tawadhu’). This research aims to determine (1) the role of teachers in shaping the character of students at Pondok Pesantren Putra Al-Maliki 1 Bahrul Ulum Tambakberas Jombang, and (2) the supporting and inhibiting factors that affect the character formation of students at the pesantren. The method used in this study is descriptive qualitative research, located at Pondok Pesantren Putra Al-Maliki 1 Bahrul Ulum Tambakberas Jombang, which is led by Drs. KH. Fadhullah Malik, M.H.I., as the supervisory board of YPPBU. Data were obtained through observation, interviews, and documentation, which were then analyzed using data analysis techniques and data validity tests. The results indicate that the supporting factors for character formation of students at Al-Maliki 1 include (1) regular Quran recitation, (2) gotong royong (collective work practice), (3) congregational prayers, and (4) discussions about morals. Meanwhile, the inhibiting factors include (1) personal issues related to consistency, (2) the external environment, and (3) lack of supervision and peer pressure. The steps taken by teachers in the process of character formation of students include (1) the exemplary method, (2) the advice method, (3) the discipline habituation method, and (4) the takziran method (punishment). The main conclusion of this study is the importance of the role of teachers in shaping the character of male students at Pondok Pesantren Al-Maliki 1 Bahrul Ulum Tambakberas Jombang, where teachers serve not only as academic educators but also as moral exemplars and character guides.